Beveragraphy: Revisiting the Typology of Food Writing from the Perspective of Culinary Linguistics - Yustin Sartika; Luthfie Arguby Purnomo; Lilik Untari; Lukfianka Sanjaya Purnama (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
From the perspectives of culinary linguistics, food writing typology, as proposed by Gerhardt, circumnavigates around food recipes, restaurant menus, and food labeling. This study attempts to propose the fourth food writing type, beveragraphy, which deals with beveragraphs or writings on drinking wares and the drink or liquid itself. This phenomenon of beveragraphy has caught Indonesian coffee shops by storm. To prove the existence of beveragraphy, we investigated this type of food writing by visiting 20 coffee shops, examined 60 beveragraphs, and interviewed the coffee shop managers, baristas, and customers. To prove that beveragraphy deserves a scholarly attention in the studies of food writing, we attempted to reveal its characteristics and functions by implementing the theory of food writing by Gerhardt, text typology by Reiss, meta-narrative loss in food discourse by Srinivas, and archetype theory in brand setting by Mark and Pearson. The findings indicate that beveragraphy is characterized by spatial restrictive writing and it functions as narrative and archetype synchronization. Future studies might employ the findings as a point of departure in food writing discourse.